2003
DOI: 10.1074/jbc.m305849200
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium botulinum C2 Toxin

Abstract: The binary Clostridium botulinum C2 toxin consists of two individual proteins, the transport component C2II (80 kDa) and the enzyme component C2I, which ADPribosylates G-actin in the cytosol of cells. Trypsin-activated C2II (C2IIa) forms heptamers that bind to the cell receptor and mediate translocation of C2I from acidic endosomes into the cytosol of target cells. Here, we report that translocation of C2I across cell membranes is accompanied by pore formation of C2IIa. We used a radioactive rubidium release a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…This suggests that ion-ion interactions between the positively charged molecules and the channel-forming heptamers are at least partially responsible for their high affinity to the C2II channel (32). Channel block occurs also when C2I is added to the cis side of C2II reconstituted into lipid bilayers at very low C2I concentration (26). Binding of EF/LF to PA is also highly ionic strength-dependent, which is presumably caused by a number of negatively charged amino acids localized within the vestibule of the PA channel (35, 44 -46).…”
Section: Discussionmentioning
confidence: 95%
“…This suggests that ion-ion interactions between the positively charged molecules and the channel-forming heptamers are at least partially responsible for their high affinity to the C2II channel (32). Channel block occurs also when C2I is added to the cis side of C2II reconstituted into lipid bilayers at very low C2I concentration (26). Binding of EF/LF to PA is also highly ionic strength-dependent, which is presumably caused by a number of negatively charged amino acids localized within the vestibule of the PA channel (35, 44 -46).…”
Section: Discussionmentioning
confidence: 95%
“…It readily became evident that pore formation by C2IIa is absolutely dependent upon both acidic conditions and binding of C2IIa to the cellular receptor prior to acidification of the medium. C2I does not interact with membrane-inserted C2IIa pores [71], thus the amount of rubidium released from cells through the C2IIa pores does not decrease in the presence of C2I. Additionally, cells treated this way do not round up [71].…”
Section: Translocation Of C2 Toxin From Acidic Endosomes Into the Cytmentioning
confidence: 92%
“…For example, pore formation by C2IIa in cell membranes can be measured independently of C2I by monitoring the efflux of radioactive rubidium-86 from preloaded cells [71]. It readily became evident that pore formation by C2IIa is absolutely dependent upon both acidic conditions and binding of C2IIa to the cellular receptor prior to acidification of the medium.…”
Section: Translocation Of C2 Toxin From Acidic Endosomes Into the Cytmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly to the anthrax toxins, the cell-bound C2I/C2IIa, Ia/Ib, and CDTa/CDTb complexes are internalized by receptor-mediated endocytosis [62][63][64][65]. After endocytosis, these complexes reach endosomal vesicles where the A components translocate across the endosomal membranes into the cytosol, possibly using the C2IIa and Ib pores as translocation corridors [61,[65][66][67][68][69][70]. in vitro model bilayer experiments have showed that PA 63 is able to bind and translocate His-tagged C2I, while C2II binds, but does not translocate LF and EF [71].…”
Section: Clostridial Binary Toxin B Subunits Are Close Orthologs Of Tmentioning
confidence: 99%